Global alcohol markets: Evolving consumption patterns, regulations and industrial organizations - Kym Anderson; Giulia Meloni; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2018)
For millennia alcoholic drinks have played an important role in food security and health (both positive and negative), but consumption patterns of beer, wine and spirits have altered substantially over the past two centuries. So too have their production technologies and industrial organization. Globalization and economic growth have contributed to considerable convergence in national alcohol consumption patterns. The industrial revolution contributed to excess consumption by stimulating demand and lowering the cost of alcohol. It also led to concentration in some alcohol industries, expecially brewing. In recent years the emergence of craft producers has countered firm concentration and the homogenization of alcoholic beverages. Meanwhile, governments have intervened extensively in alcohol markets to reduce excessive consumption, raise taxes, protect domestic industries and/or ensure competition. These regulations have contributed to, and been affected by, evolving patterns of consumption and changing structures of alcohol industries.
Keywords: 330; Globalization of preferences; Convergence of national beverage consumption mix; Alcohol and health; Restrictions on alcohol consumption and production; Beverage firm concentration